Assessing student satisfaction in business mathematics using net promoter score - Kapi, Azyan Yusra; Suhaimi, Azrina; Hasmy, Harshida; Ab Jabal, Mohamad Faizal (Penerbit UiTM (UiTM Press), 2025)
Assessing student satisfaction with instructional practices is critical to fostering engagement and improving educational outcomes, particularly in quantitative subjects such as business mathematics. This study investigates the use of the Net Promoter Score (NPS) as a metric for evaluating student satisfaction with structured practice exercises in an undergraduate business mathematics course. The course included three key topics: Trade and Cash Discounts, Markup and Markdown, and Instalment Purchase, each supported by a dedicated practice exercise designed to reinforce both conceptual understanding and practical skills. To capture student satisfaction, an NPS survey was administered to 64 students after they completed the exercises, asking them to rate their likelihood of recommending the practice sessions to their peers. Responses were categorised into Promoters, Passives, and Detractors, resulting in an overall NPS score of 77, reflecting a high level of satisfaction among participants. Additional analysis compared satisfaction levels across the three topics, providing insights into specific areas where instructional design effectively met student needs. The findings underscore the utility of NPS as a simple yet effective tool for measuring student satisfaction in educational settings, offering valuable insights that can guide curriculum design and instructional practices. This study contributes to the field of educational assessment by demonstrating the applicability of NPS for providing rapid, interpretable feedback on targeted learning activities, particularly in courses where structured practice is essential to student success.